Post-COVID and ME/CFS - do we need new disease theories? - Schauenburg, Henning (Zeitschrift für psychosomatische Medizin und Psychotherapie, 2023)
Background and Research Question: The SARS-CoV-2 pandemic often resulted in prolonged illness courses. A particular challenge today lies in the clinical presentation resembling that of Myalgic Encephalitis/Chronic Fatigue Syndrome (ME/CFS). Method: We review selected literature concerning the psychosocial factors influencing chronic courses characterized primarily by fatigue. Additionally, we explore the neurobiologically grounded theory of "Predictive Coding" as a possible explanatory framework for complex somato-psychic interactions. Results: Physical findings only partially account for the dynamics and progression of chronic fatigue syndromes, necessitating more intricate disease models that incorporate aspects of bodily perception. Conclusion: Incorporating these newer theories of perception and behavior could provide a more helpful perspective on phenomena such as fatigue, leading to improved therapeutic support measures, all without contributing to premature attributions of "psychological" causes and the associated risk of stigmatization.
Gesehen am 29.05.2024
Online veröffentlicht: Januar 2024